Graphene absorber on an SOI chip for active and passive mode locking of lasers - Tom Reep; Cheng-Han Wu; Didit Yudistira; Steven Brems; Inge Asselberghs; Marianna Pantouvaki; Joris Van Campenhout; Dries Van Thourhout; Bart Kuyken (Scientific Reports)
Abstract We demonstrate both passive and active mode-locking of fiber lasers using a graphene-based absorber integrated on a silicon photonics platform manufactured using a wafer-scale CMOS process. Passive mode-locking is achieved at a 28 MHz repetition rate, generating 1.7 ps optical pulses, while active mode-locking is demonstrated at repetition rates of 4 GHz and 10 GHz. This work demonstrates the potential of scalable graphene-based saturable absorbers for fiber laser locking and paves the way for future fully integrated mode-locked laser systems.